Digital preservation initiatives in the United States: a summary - Marcum, Deanna (2003)
General presentation on how digital preservation issues are being faced in the United States of America. Special reference to the National Digital Information Infrastructure and Preservation Program, that is found at the Library of Congress, and aims to implement a national strategy for the long-term preservation of digital content.